Physicochemical properties of pineapple plant waste fibers from the leaves and stems of different varieties - Zainuddin, Muhammad Fakhri; Shamsudin, Rosnah; Mokhtar, Mohd Noriznan; Ismail, Dahlan (North Carolina State University, 2014)
Pineapple agro-waste, the residue produced during harvesting or processing activities, is widely available around the world. After harvesting, most pineapple residue is disposed of and serves as fertilizer, or is burnt in an open field. However, these methods are not only ineffective, but also contribute to air pollution. The main objective of this study is to determine the physicochemical properties (i.e., cellulose, hemicellulose, lignin, proximate composition, dry matter, and nitrogen content), of leaves and stems in different varieties (MD2, Moris, and Josapine) of the pineapple plant waste. The data obtained were analyzed using thermogravimetry analysis and proximate analysis. The results showed that the stems and leaves of different varieties exhibit different percentages in lignocellulosic content (hemicellulose, cellulose, and lignin). Proximate analysis showed that nutrient contents were available in the leaves and stems of pineapple plant of different varieties.